2017
DOI: 10.1021/acs.jproteome.7b00017
|View full text |Cite
|
Sign up to set email alerts
|

Malonylome Analysis Reveals the Involvement of Lysine Malonylation in Metabolism and Photosynthesis in Cyanobacteria

Abstract: As a recently validated reversible post translational modification, lysine malonylation regulates diverse cellular processes from bacteria to mammals, but its existence and function in photosynthetic organisms remain unknown. Cyanobacteria are the most ancient group of photosynthetic prokaryotes and contribute about 50% of the total primary production on Earth. Previously, we reported the lysine acetylome in the model cyanobacterium Synechocystis sp. PCC 6803 (Synechocystis). Here we performed the first proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 87 publications
1
20
0
Order By: Relevance
“…Overall, 506 Kmal sites across 326 proteins were detected. The number of Kmal proteins in T. gondii was higher than that reported in common wheat, S. erythraea (Xu et al, 2016;Liu et al, 2018), but was lower than that detected in E. coli (Qian et al, 2016), rhizobacterium Bacillus amyloliquefaciens FZB42 (Fan et al, 2017) and mammals (Colak et al, 2015), however was close to the number of malonylated proteins identified in Cyanobacteria (Ma et al, 2017). As shown in Figure 1B, a total of 326 proteins were modified/malonylated at more than two lysine residues.…”
Section: Global Detection Of Kmal Sites On T Gondii Proteinsmentioning
confidence: 53%
See 1 more Smart Citation
“…Overall, 506 Kmal sites across 326 proteins were detected. The number of Kmal proteins in T. gondii was higher than that reported in common wheat, S. erythraea (Xu et al, 2016;Liu et al, 2018), but was lower than that detected in E. coli (Qian et al, 2016), rhizobacterium Bacillus amyloliquefaciens FZB42 (Fan et al, 2017) and mammals (Colak et al, 2015), however was close to the number of malonylated proteins identified in Cyanobacteria (Ma et al, 2017). As shown in Figure 1B, a total of 326 proteins were modified/malonylated at more than two lysine residues.…”
Section: Global Detection Of Kmal Sites On T Gondii Proteinsmentioning
confidence: 53%
“…Lysine malonylation was firstly observed in mammalian cells and bacterial cells (Lin et al, 2012). Since then, there have been growing interests in exploring the regulatory roles of Kmal in various microbial species, such as Escherichia coli (Qian et al, 2016), Cyanobacteria (Ma et al, 2017), and Saccharopolyspora erythraea (Xu et al, 2016). Although Kmal can regulate many crucial and diverse cellular processes (He et al, 2012), its existence and function in T. gondii remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as a result of advancements in liquid chromatography-tandem mass spectrometry (LC-MS/MS), a large number of lysine-acetylated proteins have been identified [ 2 ]. However, compared to these acetylation profiles, only a few organisms have been studied with respect to lysine malonylation, including Bacillus amyloliquefaciens [ 4 ], Escherichia coli [ 5 ], Saccharopolyspora erythraea [ 10 ], cyanobacteria ( Synechocystis ) [ 11 ], rice [ 12 ], HeLa cells [ 9 ], and mice [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ksucc regulated the activity of acetyl-coenzyme A synthetase (Acs) in Mycobacterium tuberculosis ( 33 ). Lysine malonylation was involved in metabolism in E. coli and photosynthesis in Cyanobacteria ( 9 , 34 ) . Given the important biological significance of the above-listed lysine PTMs in prokaryotes, it is conceivable to anticipate that Khib also likely regulates the protein function and thereby modulates the physiological processes in prokaryotes.…”
Section: Discussionmentioning
confidence: 99%